Analisis Suatu Peradilan Hukum Terhadap Pelaku Genosida Pada Masyarakat - Faturohman Faturohman; Siti Nurfadila Apiati; Laila Arofah (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
Genocide is a serious crime, which includes an act of massacre against an ethnic or religious group with the aim of destroying the existence of that group. The existence of legal action against the perpetrators of this genocide can be a very crucial issue in efforts to uphold justice, and can also prevent the recurrence of similar crimes in the future. The process of carrying out a trial against the perpetrators of this genocide, starting from an arrest to a trial and also the imposition of punishment. There is a role for an institution that is carried out internationally, such as the existence of a criminal trial carried out by the International, and also the existence of a national legal mechanism that can also overcome the crime of genocide. The existence of a process in this court can face various challenges and the collection of evidence is very adequate. Not only that, the overlap between national and international courts can add complexity to the legal process.